EVALUASI PENYELESAIAN TINDAK LANJUT REKOMENDASI HASIL AUDIT BPK SEBAGAI KEY PERFORMANCE INDICATOR - Siti Kurniati; Yulianti Abbas (Owner : Riset dan Jurnal Akuntansi, 2023)
Using SMART criteria and Institutional Isomorphism perspective, this study intends to evaluate the Audit Board of The Republic of Indonesia (BPK)’s audit recommendation follow-up at the Directorate General Z. Although the audit recommendation follow-up has been Directorate General Z’s Key Performance Indicator (KPI) since 2018, it still fails to complete all recommendations within the last five years. This study intends to identify factors causing the non-optimal completion of the follow-up of BPK's audit as the institution’s KPI. This study uses a qualitative approach with a case study as well as content analysis and Miles and Huberman's model for analyzing the interview results. The results show that the KPI related to the follow-up on BPK recommendations have not fully met the SMART criteria, namely (1) Measurable; and (2) Achievable/Attainable criteria. Thus, this study suggests an adjustment to KPI is needed to ensure a full completion of audit recommendation follow up. Additionally, institution needs to account for factors that may influence KPI adjustment, namely the involvement of external parties, employee performance incentives, innovation, and society’s expectations.